Curvature Analysis of Seed Silhouettes in Silene L - Cervantes, Emilio; Rodríguez-Lorenzo, José Luis; Martín-Gómez, José Javier; Tocino, Ángel (Plants (Basel, Switzerland), 2023)
The application of seed morphology to descriptive systematics requires methods for shape analysis and quantification. The complexity of lateral and dorsal views of seeds of Silene species is investigated here by the application of the Elliptic Fourier Transform (EFT) to representative seeds of four morphological types: smooth, rugose, echinate and papillose. The silhouettes of seed images in the lateral and dorsal views are converted to trigonometric functions, whose graphical representations reproduce them with different levels of accuracy depending on the number of harmonics. A general definition of seed shape in Silene species is obtained by equations based on 40 points and 20 harmonics, while the detailed representation of individual tubercles in each seed image requires between 100 and 200 points and 60-80 harmonics depending on their number and complexity. Smooth-type seeds are accurately represented with a low number of harmonics, while rugose, echinate and papillose seeds require a higher number. Fourier equations provide information about tubercle number and distribution and allow the analysis of curvature. Further estimation of curvature values in individual tubercles reveals differences between seeds, with higher values of curvature in S. latifolia, representative of echinate seeds, and lower in S. chlorifolia with rugose seeds.
Keywords: morphology; systematics; development; curvature; Elliptic Fourier Transform; Bézier curve; complexity; seed; models